Carbon Nanotube Reinforced Hydroxyapatite Nanocomposites As Bone Implants: Nanostructure, Mechanical Strength And Biocompatibility - Lawton, Kiruthika (Int J Nanomedicine, 2019)
PURPOSE: Hydroxyapatite (HA) is a biologically active ceramic which promotes bone growth, but it suffers from relatively weak mechanical properties. Multi-walled carbon nanotubes (MWCNTs) have high tensile strength and a degree of stiffness that can be used to strengthen HA; potentially improving the clinical utility of the bone implant. METHODS: HA was precipitated by the wet precipitation method in the presence of pristine (p) or functionalised (f) MWCNTs, and polyvinyl alcohol (PVA) or hexadecyl trimethyl ammonium bromide (HTAB) as the surfactant. The resulting composites were characterised and the diametral tensile strength and compressive strength of the composites were measured. To determine the biocompatibility of the composites, human osteoblast cells (HOB) were proliferated in the presence of the composites for 7 days. RESULTS: The study revealed that both the MWCNTs and surfactants play a crucial role in the nucleation and growth of the HA. Composites made with f-MWCNTs were found to have better dispersion and better interaction with the HA particles compared to composites with p-MWCNTs. The mechanical strength was improved in all the composites compared to pure HA composites. The biocompatibility study showed minimal LDH activity in the media confirming that the composites were biocompatible. Similarly, the ALP activity confirmed that the cells grown on the composites containing HTAB were comparable to the control whereas the composites containing PVA surfactant showed significantly reduced ALP activity. CONCLUSIONS: The study shows that the composites made of f-MWCNTs HTAB are stronger than pure HA composites and biocompatible making it a suitable material to study further.